Utilization of E-KTP as Home Safety Using Arduino Nano Based on Android - Mustolih, Riyanto; Lenggana, U Tresna; Mulyana, Jajang (JOIN (Jurnal Online Informatika), 2019)
Security is an absolute necessity for every homeowner so that he can create a sense of security and calm when the house is left to travel by the owner of the house. Poor security makes the house a target for theft. Home security currently used still uses conventional methods. E-KTP (Electronic Identity Card) provided by the government to every citizen has a technology in which there is an RFID chip that can be used as a substitute for conventional door locks. In order for the e-KTP to be able to access the home door, an application needs to be made that can be used on android smartphone. The application makes it easy for homeowners in the E-KTP registration process that can be used to open the door. In addition, the application can send notifications to homeowners if the house is entered by thieves via SMS (Short Message Service) and Call / Call through the SIM800L module which is controlled using an Arduino Nano Microcontroller.